SENSITIVITY ANALYSIS BASED ON THE FORCE METHOD FOR DEPLOYABLE CABLE-STIFFENED STRUCTURES - YOU, Z. (Engineering optimization, 1997)
The force method is an ideal structural analysis tool when dealing with prestress and internal mobility. This paper presents a sensitivity analysis for the internal forces and nodal displacements of a structure with respect to key design variables such as structural configurations, member cross-sectional areas and material parameters, etc, this analysis, though limited to small displacements and rotations of liner elastic structures, provides a useful tool in the structural design process for tasks such as minimizing weight, maximizing stiffness or achieving a better distribution of prestress. The method proposed is applied to the optimization of a cable-stiffened deployable mast, where the lowest mass has been sought subject to a given stiffness requirement.